Circadian Misalignment and Social Jetlag: Consequences for Physical Performance and Injury Risk in Young Adults. - Sikorska, Alicja; Mian, Emil; Zapart, Zuzanna; Szepietowska, Martyna; Nowicka, Nina; Bundyra, Jakub; Sochocka, Agata; Gańska, Oliwia; Janik, Dominika; Parda, Julia (Quality in Sport, 2026)
Background. Circadian rhythms, governed by the suprachiasmatic nucleus and peripheral oscillators in skeletal muscle, regulate peak physiological performance windows. Social jetlag (SJL) - the discrepancy between biological time and social schedules - is highly prevalent in young adults due to a developmental shift toward "eveningness". Aim. This narrative review aims to synthesize current evidence regarding the impact of SJL on physical performance metrics and musculoskeletal injury risk in the young adult demographic. Material and method. A narrative synthesis of articles (systematic reviews, meta-analyses, and experimental studies) published between 2005 and 2026 was conducted. Analysis focused on cardiorespiratory fitness, neuromuscular power, and longitudinal injury data in tactical and athletic populations. Results. High levels of SJL (≥ 1.5-2 hours) are significantly associated with reduced cardiorespiratory fitness ( peak), particularly in males. In anaerobic domains, SJL blunts the natural diurnal rhythm of explosive power, resulting in lower vertical jump performance and reduced maximal voluntary contraction during morning training. Furthermore, prospective data from ROTC cohorts demonstrate that SJL is a robust behavioral predictor of musculoskeletal injury, with injured individuals exhibiting nearly double the SJL magnitude of their uninjured peers. Conclusions. Chronic circadian misalignment acts as a systemic "performance inhibitor" and a significant risk factor for injury. Mitigation requires "circadian literacy" in coaching and the implementation of chronotype-adjusted training schedules to align physical demands with endogenous biological windows.